Negotiating neoliberalism : developing alternative educational visions. - Rudd, Tim (Studies in professional life and work., 2017)
This book highlights the central features of neoliberal education policies, their origins, recent developments and also their inherent weaknesses and flaws. The various chapters challenge the common assumption that the neoliberal project is a monolithic orthodoxy by highlighting its complexities, variations and contradictions in the ways policies are refracted through action and practice in different contexts. The book also challenges the common assumption that there are no viable alternatives to neoliberal education policies. It is argued that such alternatives not only highlight the range of different approaches, choices and possibilities but also provide the seedbed for a reimagined educational future. The authors offer a range of conceptual and theoretical insights and analyses that highlight the weaknesses and limitations inherent within the neoliberal education project and also illustrate the dangers in following the prevailing hegemonic discourse and trajectories. It is postulated that alternative educational approaches warrant greater and urgent attention because history suggests that rather than having weathered the recent economic crisis, we may well be witnessing the long tail of decline for the neoliberal project.